The impact of digital storytelling strategy on developing skills in constructing a polyphonic environment for a historical character in children's theater performances (Al-Academy, 2025)
Contemporary education has placed great emphasis on the learner, who is the foundation of the educational process. Therefore, educational institutions of all kinds have sought to develop the latest strategies, methods, digital tools, and educational programs to keep pace with the demands of the era and its scientific and technological developments. In line with contemporary developments and the latest in digital education technologies, the researcher focused on digital stories, given their tremendous potential to enrich educational situations with stimulating elements and audio and visual effects. This makes the educational process more enjoyable, exciting, and creative, and benefits both teachers and learners alike, making the educational process more interactive and effective. Digital stories are a modern technology designed, produced, and presented via computer. Teachers can use them in the classroom, and they represent a transformation in education, shifting from the usual method of explanation to a focus on advanced learning skills, such as comprehension and innovation. This technology presents information to learners through comprehensive programs rich in colorful graphics, movements, and sound effects to create a polyphonic environment for historical figures in children's theater performances. This study examined how using digital storytelling could improve the ability of art education students, specializing in school theater, to build a polyphonic setting for a historical figure in children's plays. The study employed an experimental method, comparing a control and an experimental group. The sample included 62 students. A skill test was created to evaluate the construction of the polyphonic environment, ensuring its validity and dependability. Two third-year classes from Al-Mustansiriyah University's College of Basic Education, Department of Art Education (morning classes), were randomly selected: one served as the control group (31 students), using traditional methods, and the other was the experimental group (31 students), using the digital storytelling approach. The results revealed substantial differences favoring the experimental group, which used the digital storytelling approach, when contrasted with the control group, which used the traditional method. Based on these findings, the research offered conclusions, suggestions, and recommendations.